Case study : how synaptic health alliance used Blockchain to improve data management (O'Reilly Media, Inc., 2021)
Healthcare providers spend billions of dollars annually on data management, yet provider directories often contain inaccuracies that dramatically increase the cost of care while reducing its quality. In response, Aetna, Humana, MultiPlan, Quest Diagnostics, and UnitedHealth Group have formed the Synaptic Health Alliance to explore the use of blockchain technology in tackling the challenge of accurate and efficient provider data management and sharing. Join us for this Case Study with UnitedHealthcare's Meyrick Vaz to learn more about the Synaptic Health Alliance, better understand why it was founded, and explore the potential of blockchain for solving some of data management's biggest challenges. You'll examine the current state of provider data exchange as well as the goals, approach, and results of the initial pilot project for the alliance. Recorded on November 18, 2021. See the original event page for resources for further learning or watch recordings of other past events. O'Reilly Case Studies explore how organizations have overcome common challenges in business and technology through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and challenges while hearing their unique perspectives, insights, and lessons learned.